BENEFIT ANALYSIS OF COAL UNIT UTILITIES AT PT PETROKIMIA GRESIK FERTILIZER PLANT - (NIM : 22109315), NURFITRIANA
The limited resources and the rising prices of natural gas are creating a problem for the fertilizer industry. At PT Petrokimia Gresik fertilizer plant, the natural gas are used as a raw material for the production and an energy source. Energy diversification efforts are being made by using coal as an alternative energy source for power generation, through the construction of Coal Unit Utilities (CUU). CUU boiler capacity consists of 2x150 tons of steam per hour and the power generation capacity is 25 MW. While the CUU is operating, natural gas savings occur at 1.576.979 MMBTU/year, MFO savings occur at 3.718 m3/year, and electricity savings of 123.692.000 KWh/year. The benefit-cost analysis was done to determine the amount of gain or loss that might occur as well as the feasibility of the project. The costs that were included are the cost of the initial investment and operating costs of the CUU. Benefits are calculated based on energy cost savings after CUU operate and sales of coal combustion ash at CUU. Analysis conducted using two scenarios of cash flows to determine the effect of price increases on investment feasibility. Despite the price increase, the results obtained are still optimal at NPV on US$ 87.752.614, a 27% IRR, and payback period of 4 years. B/C Ratio analysis produces a value of 1.82 indicates the benefits outweigh the costs issued. Energy cost savings can be used to increase the plant's production capacity or as capital to build new plant. This will also reduce the cost of fertilizer production and subsidies issued by the government. The use of coal is expected to reduce dependence on natural gas for fertilizer industry and support a national energy policy to achieve an optimal energy mix.